Methods Dentists Use to Diagnose Primary Caries Lesions Prior to Restorative Treatment: Findings from The Dental PBRN - Rindal, D. Brad (2010)
OBJECTIVE: To (1) quantify the diagnostic techniques used by Dental Practice-Based Research Network (DPBRN) dentists before they decide to treat primary caries lesions surgically and (2) examine whether certain dentist, practice, and patient characteristics are associated with their use. METHODS: A total of 228 DPBRN dentists recorded information on 5,676 consecutive restorations inserted due to primary caries lesions on 3,751 patients. Practitioner-investigators placed a mean of 24.9 (SD=12.4) restorations. Lesions were categorized as posterior proximal, anterior proximal, posterior occlusal, posterior smooth, or anterior smooth. Techniques used to diagnose the lesion were categorized as clinical assessment, radiographs, and/or optical. Statistical analysis utilized generalized mixed-model ANOVA to account for the hierarchical structure of the data. RESULTS: By lesion category, the diagnostic technique combinations used most frequently were clinical assessment plus radiographs for posterior proximal (47%), clinical assessment for anterior proximal (51%), clinical assessment for posterior occlusal (46%), clinical assessment for posterior smooth (77%), and clinical assessment for anterior smooth (80%). Diagnostic technique was significantly associated with lesion category after adjusting for clustering in dentists (p<0.0001). CONCLUSION: These results — obtained during actual clinical procedures rather than from questionnaire-based hypothetical scenarios — quantified the diagnostic techniques most commonly used during the actual delivery of routine restorative care. Diagnostic technique varied by lesion category and with certain practice and patient characteristics.